Risk-reducing salpingo-oophorectomy in BRCA1 and BRCA2 mutated patients: An evidence-based approach on what women should know. (December 2017) - De Felice, F.; Marchetti, C.; Boccia, S.M.; Romito, A.; Sassu, C.M.; Porpora, M.G.; Muzii, L.; Tombolini, V.; Benedetti Panici, P.
Highlights: The risk of ovarian cancer (OC) in BRCA mutation carries represents a common entity. The risk-reducing salpingo-oophorectomy (RRSO) is the mainstay treatment approach. Several topics, such as timing, side effects and hormone therapy, need to be clarified. These open questions are analyzed, based on recent published data. Abstract: This review is focused on the ovarian cancer risk reduction management in BRCA mutation carriers and is intended to assist with clinical decision-making. Obviously, treatment decisions must be based on the available evidence. Despite risk-reducing salpingo-oophorectomy is firmly recommended, several separate questions can be raised to address the variety of intense controversy of this approach. A special emphasis lies in the effective preventive surgical measure against ovarian cancer risk, in an attempt to detect the optimal timing and mitigate the impact on patients. The long term implications of risk-reducing salpingo-oophorectomy as well as hormone replacement therapy are also actively debated. This is expected to represent an opportunity for improved management modelling of BRCA mutated patients.